The expanded field of printmaking: its intersections and counterpoints with writing and the image in the context of contemporary art - Veneroso, Maria do Carmo de Freitas (PORTO ARTE: Revista de Artes Visuais, 2013)
In this article I present how the changes on the statute of printmaking during the 20th century and continuing in the 21st century has enabled an approach of printing practices from the perspective of an “extended” or “expanded field”, in which printmaking dialogues with other languages such as writing. Writing is approached through the fabric of the visual text, its “graphic texture”, in the Barthesian meaning. By referring to graphic texture, Barthes draws a relation with the origin of writing in a time when drawing, engraving and writing were very close activities.